Effects of tooth preparation on the microleakage of fissure sealant - Gesti Kartiko Sari; Sri Kuswandari; Putri Kusuma Wardani Mahendra (Dental Journal (Majalah Kedokteran Gigi), 2022)
Background: Fissure sealing can be achieved by preparing and sealing the deep pits and fissures in the teeth with a sealant to prevent caries. Fissure sealing is performed using resin modified glass ionomer cement (RMGIC) and failure is most often due to weak adhesion between the material and the tooth, resulting in microleakage. Purpose: The study aimed to determine the effect of a preparation technique with bur and acid application on potential RMGIC fissure sealant microleakage. Methods: Twenty-four extracted maxillary premolars were divided into four treatment groups. Group 1 underwent enameloplasty with a round bur and application of 37% phosphoric acid; group 2 with a tapered bur and 37% phosphoric acid; group 3 with a round bur and 10% polyacrylic acid; and group 4 with a tapered bur and 10% polyacrylic acid. The application of 37% phosphoric acid was carried out for 15 seconds, while 10% polyacrylic acid was applied for 20 seconds, before RMGIC filling. The teeth were stored in artificial saliva at 37°C for 24 hours, then thermocycled 100 times at 5°C and 55°C for 20 seconds each. The teeth were immersed in a 1% methylene blue solution for 24 hours at 37°C, then cut crosswise. The length of the microleakage was observed with a stereo microscope at 8 times magnification and measured using raster image application. Data was analysed with one-way ANOVA. Results: Significant differences were found between treatment groups (F=562.14; p<0.05). The deepest mean microleakage was in the round bur and 10% polyacrylic acid group (1657.87 ± 78.08) and the shallowest was in the round bur and 37% phosphoric acid group (500.70 ± 38.55). Conclusion: The preparation method, type of bur and acid solution have an effect on microleakage potential of RMGIC fissure sealing. Round bur preparation and 37% phosphoric acid resulted in shallow microleakage.